Computed tomography-guided argon-helium cryoablation for sacrum chordoma. Issue 42 (16th October 2020) - Li, Liang; Jiang, Xiao-Fan; Sun, Li-Jun; Fu, Yu-Fei; Zhang, Wei
Abstract : Abstract: We examined the therapeutic effects of argon-helium cryoablation guided by computed tomography (CT) in the treatment of sacral chordoma. This is a retrospective study. CT-guided argon-helium cryoablation was used to treat 9 sacral chordoma patients at our centers between January 2016 and June 2019. We collected data on treatment response and success. Data from long-term follow-up of treatment outcomes were also assessed. All patients were treated successfully according to the indicated technical parameters. There were no reports of procedure-related complications from any of the patients. Complete response (CR) was also achieved in all patients. Six patients (66.7%) achieved initial CR after 1 treatment session and 3 patients (33.3%) achieved secondary CR after 2 treatment sessions. The chordoma-related symptoms improved significantly in all patients after treatment. The mean visual analogue scale score improved from 7.3 before treatment to 4.2 after treatment ( P < .001). The mean function score improved from 3.2 before treatment to 1.4 after treatment ( P < .001). The median length of follow-up for all patients was 33 months (range: 6–46 months). All patients were alive during the follow-up. Two (22.2%) patients experienced local recurrence (LR) at 6 and 9 months after treatment, respectively. These patients had revised treatment with trans-arterial embolism (n = 1) or repeat ablation (n = 1). The median progression-free survival was 36.8 months. Treatment of sacral chordoma with CT-guided argon-helium cryoablation is effective and offers a potentially beneficial therapeutic alternative for patients with the condition.